Predicting low disease activity and remission using early treatment response to antitumour necrosis factor therapy in patients with rheumatoid arthritis: exploratory analyses from the TEMPO trial. Issue 2 (13th October 2011) - Curtis, Jeffrey R; Yang, Shuo; Chen, Lang; Park, Grace S; Bitman, Bojena; Wang, Brian; Navarro-Millan, Iris; Kavanaugh, Arthur
Abstract : Objective: To derive and validate decision trees to categorise rheumatoid arthritis (RA) patients 12 weeks after starting etanercept with or without methotrexate into three groups: patients predicted to achieve low disease activity (LDA) at 1 year; patients predicted not to achieve LDA at 1 year and patients who needed additional time on therapy to be categorised. Methods: Data from RA patients enrolled in the TEMPO trial were analysed. Classification and regression trees were used to develop and validate decision tree models with week 12 and earlier assessments that predicted long-term LDA. LDA, defined as disease activity score in 28 joints (DAS28) ≤3.2 or clinical disease activity index ≤10.0, was measured at 52 or 48 weeks. Demographics, laboratory data and clinical data at baseline and to week 12 were analysed as predictors of response. Results: 39% (67/172) of patients receiving etanercept and 60% (115/193) of patients receiving etanercept plus methotrexate achieved LDA at week 52. For patients receiving etanercept, 53% were predicted to have LDA, 39% were predicted not to have LDA and 8% could not be categorised using DAS28 criteria at week 12. For patients receiving etanercept plus methotrexate, 63% were predicted to have LDA, 25% were predicted not to have LDA and 12% could not be categorised. Conclusion: Most (80–90%) patients in TEMPO initiating etanercept with or without methotrexate could be predicted within 12 weeks of starting therapy as likely to have LDA or not at week 52. However, approximately 10–20% of patients needed additional time on therapy to decide whether to continue treatment.